2016
DOI: 10.1038/srep38087
|View full text |Cite
|
Sign up to set email alerts
|

Chemotypic variation in terpenes emitted from storage pools influences early aphid colonisation on tansy

Abstract: Tansy plants (Tanacetum vulgare L.) exhibit high chemical variation, particularly in mono- and sesquiterpenes that are stored in specialised glands on the plant surface. In the present work we investigated the effects of terpene chemotypes on Metopeurum fuscoviride, an aphid species specialised on tansy, and their tending ants, at the field scale. Previous studies have chemotyped tansy by assessing dominant compounds; here we propose a method of chemotyping using all volatile compounds that are likely emitted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
132
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 48 publications
(140 citation statements)
references
References 50 publications
8
132
0
Order By: Relevance
“…The presence of ants on tansy plants, before aphid colonisation, was recently shown to vary across different plant chemotypes, suggesting they are attracted or repelled by certain chemical compounds emitted by the plant (Clancy et al, 2016). floral nectaries) were not present in the early and mid-season, ants were present on currently unoccupied tansy plants.…”
Section: Mutualistsmentioning
confidence: 99%
“…The presence of ants on tansy plants, before aphid colonisation, was recently shown to vary across different plant chemotypes, suggesting they are attracted or repelled by certain chemical compounds emitted by the plant (Clancy et al, 2016). floral nectaries) were not present in the early and mid-season, ants were present on currently unoccupied tansy plants.…”
Section: Mutualistsmentioning
confidence: 99%
“…In addition to variation in the VOCs, we showed-through untargeted metabolomic profiling of the leaves-that all plants of certain metabotypes (clusters of plants with similar metabolomic profiles) were colonised by aphids at the peak of the season (even on "less preferred" volatile chemotypes) (Clancy et al, 2018). The two common mutualistic ant species in this system also responded to plant chemical variation (Clancy et al, 2016), and the presence of ants increased colonisation success and benefited the population growth of M. fuscoviride aphids (Flatt & Weisser, 2000;Senft, Weisser, & Zytynska, 2017). Interestingly, there was no association between plant volatile chemotype and metabotype, leading to a unique system where we can disentangle effects of these two aspects of chemical diversity (Clancy et al, 2018).…”
Section: Introductionmentioning
confidence: 88%
“…We used the plant volatile chemical information on 22 compounds, emitted from specialised storage structures on the plant (identified using GC-MS), from Clancy et al (2016), and secondary metabolite information of 1,020 mass features as identified using LC-MS by Clancy et al (2018) (for more details, see Appendix S1). Our focus was only on those plants that were colonised by aphids, so we performed new cluster analyses on these 87 plants to obtain chemotype and metabotype plant groupings, using the package "pvclust" (Suzuki & Shimodaira, 2015) in R v3.3.0 in RStudio v0.99.896.…”
Section: Plant Chemical and Clustering Analysismentioning
confidence: 99%
See 2 more Smart Citations